“An Old China Hand Who Loved the Chinese People”: Herbert Chatley (1885-1955), Civil Engineer and Historian of Chinese Science and Technology - Jami, Catherine (Annali di Ca’ Foscari: Serie Orientale)
Herbert Chatley (1885‑1955) was one of the scholars on whose research and expertise Joseph Needham drew when writing Science and Civilisation in China. Chatley worked in China for three decades, first as a teacher in Tangshan 唐山, where he trained a number of Chinese engineers and scientists, then as an engineer in charge of the dredging of the Huangpu 黃浦 river in Shanghai. His scholarship spanned a wide spectrum of fields, and therefore belonged in various spaces of circulation, including not only the global community of engineering, but also that of knowledge about China pertaining to the history of science and technology, then mostly separated from academic sinology in the West.